Neurodevelopmental Toxic Effects of Food Additives Used in Energy Drinks on Developing Rats - Revathi Boyina; Sujatha Dodoala (Tabriz University of Medical Sciences, 2021)
Background: Food additives are widely used in energy drinks and when taken above acceptable daily intake leads to various neurodevelopmental toxic effects. The present study aimed to evaluate the neurodevelopmental toxic effects in rat pups after pre and postnatal administration of selected food additives in pregnant animals. Methods: Pregnant rats aged 160-180 days were divided into six groups with four animals per group. Group 1 treated with vehicle, group 2 standard (caffeine 25 mg/kg p.o.), groups 3-6 were treated with glucuronolactone (5 mg/kg p.o.), taurine (8 mg/kg p.o.), gluconolactone (84 mg/kg p.o.), and combination of food additives respectively till postnatal day (PND) 15. After PND 21, pups were evaluated for neurobehavioural parameters using the behavioral alteration test, Morris water maze test, locomotor activity test, Y-maze test, hot plate latency and neurobehavioural scoring. Neurotransmitters were estimated in brain tissue extract on PND 30, 45 and 60 and histological observations were examined in the brain cortex region. Results: Food additive treated groups showed an increase in behavioral activity, escape latency, immobility, percentage of alterations, hot plate latency and neurobehavioural scoring at selected dose and combination compared to control (p<0.001). The decrease in neurotransmitter levels in the brain and marked degeneration of neurons in the cortex were observed significantly in group6 pups. Conclusion: The present results corroborate that food additives in combination induced neurodevelopmental toxic effects further mechanistic studies are suggested to understand the synergistic effect.